2020
DOI: 10.3390/nu12010214
|View full text |Cite
|
Sign up to set email alerts
|

Policaptil Gel Retard Intake Reduces Postprandial Triglycerides, Ghrelin and Appetite in Obese Children: A Clinical Trial

Abstract: The aim of this study is to test the hypothesis that the intake of Policaptil Gel Retard® (PGR) is able to affect appetite, metabolic and hormonal postprandial profile in obese children. 46 obese children were randomly assigned to treatment with PGR or placebo, in a double blind clinical trial. Two PGR tablets or placebo were given in fasting condition, before the ingestion of a mixed meal (15 kcal/kg lean body mass). Blood samples were taken at baseline and for 4 h, for measuring blood lipids, glucose, insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Our findings in children and adolescents with type 1 diabetes, obesity and MetS suggest that PGR significantly lowers BMI and improves adiposity parameters, supporting our previous work and the literature on severely obese children and adolescents with insulin resistance and a family history of obesity and type 2 diabetes [30][31][32].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings in children and adolescents with type 1 diabetes, obesity and MetS suggest that PGR significantly lowers BMI and improves adiposity parameters, supporting our previous work and the literature on severely obese children and adolescents with insulin resistance and a family history of obesity and type 2 diabetes [30][31][32].…”
Section: Discussionsupporting
confidence: 90%
“…The use of this compound, possibly in association with a low GI/GL diet, could lead to an improvement in the parameters associated with MetS. More specifically, a recent study by Fornari et al has shown that the intake of PGR is associated with a significant reduction in appetite, ghrelin and triglycerides in obese children, confirming the effect of PGR in affecting appetite, metabolic and hormonal postprandial profile [32]. Therefore, because of its characteristics, PGR could represent a promising treatment option in these patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The healthy effects of fibers were recently analyzed by Reynholds et al, which evaluates 45 observational studies in children aged 1 to 19 years, identifying benefits on body weight, blood lipids, blood pressure, blood glucose associated with an increased intake of fiber with the diet and high-fiber foods, in the absence of adverse events [76]. Positive effects of fiber supplementation on reducing appetite and triglycerides absorption are also demonstrated after a single intake, in the postprandial phase in the obese children [77]. For the consumption of fruit and vegetables, Bramante et al report positive results of interventions in the school environment in 2 out of 5 studies [61].…”
Section: Interventions On Specific Aspects Of Dietary Intakementioning
confidence: 99%
“…Furthermore, fibers can decrease the appetite both in obese and non-obese subjects. For these reasons, these dietetic compounds are associated with the reduction of obesity, diabetes, and cardiovascular complications (Fornari et al, 2020;Rosado et al, 2020).…”
Section: Introductionmentioning
confidence: 99%